Hunting for intermediate-mass black holes in globular clusters: an astrometric study of NGC 6441. Issue 1 (18th February 2021) - Häberle, Maximilian; Libralato, Mattia; Bellini, Andrea; Watkins, Laura L; Pott, Jörg-Uwe; Neumayer, Nadine; van der Marel, Roeland P; Piotto, Giampaolo; Nardiello, Domenico
ABSTRACT: We present an astrometric study of the proper motions (PMs) in the core of the globular cluster NGC 6441. The core of this cluster has a high density and observations with current instrumentation are very challenging. We combine ground-based, high-angular-resolution NACO@VLT images with Hubble Space Telescope ACS/HRC data and measure PMs with a temporal baseline of 15 yr for about 1400 stars in the centremost 15 arcsec of the cluster. We reach a PM precision of ∼30 µas yr −1 for bright, well-measured stars. Our results for the velocity dispersion are in good agreement with other studies and extend already existing analyses of the stellar kinematics of NGC 6441 to its centremost region never probed before. In the innermost arcsecond of the cluster, we measure a velocity dispersion of (19.1 ± 2.0) km s −1 for evolved stars. Because of its high mass, NGC 6441 is a promising candidate for harbouring an intermediate-mass black hole (IMBH). We combine our measurements with additional data from the literature and compute dynamical models of the cluster. We find an upper limit of $M_{\rm IMBH} \lt 1.32 × 10^4\, M_\odot$ but we can neither confirm nor rule out its presence. We also refine the dynamical distance of the cluster to $12.74^{+0.16}_{-0.15}$ kpc. Although the hunt for an IMBH in NGC 6441 is not yet concluded, our results show how future observations with extremely large telescopes will benefit from the long temporal baseline offered by existing high-angular-resolution data.